2016
DOI: 10.1016/j.exphem.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-phenotype acute leukemia (MPAL) exhibits frequent mutations in DNMT3A and activated signaling genes

Abstract: Mixed phenotype acute leukemia (MPAL) is a heterogeneous group of poor-prognosis leukemias with immunophenotypic features of at least two cell lineages. The full spectrum of genetic mutations in this rare disease has not been elucidated, limiting our understanding of disease pathogenesis and our ability to devise targeted therapeutic strategies. We sought to define the mutational landscape of MPAL by performing whole exome sequencing on samples from 23 adult and pediatric MPAL patients. We identified frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 22 publications
6
48
0
Order By: Relevance
“…Investigators grouped MPAL alleles into three functional groups including cell signaling pathways ( RAS, NF1, JAK ); tumor suppressors ( TP53, WT1 ) and transcription factor ( NOTCH1, RUNX1 and GATA2 ). Notably, mutations in NPM1 and PAX5 , which are the most common mutations in AML 27 and ALL 28 , respectively, were not seen in any patient in either of the described cohorts or in the cases presented in this report suggesting that these mutations may confer lineage specificity, an observation made by other recent investigators 29 . MPAL with TP53 mutations may represent inappropriate classification of therapy-related myeloid neoplasms as MPAL given that mutations in this gene are strongly associated with prior cytotoxic exposure and rarely seen in de novo leukemia 5, 30 .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Investigators grouped MPAL alleles into three functional groups including cell signaling pathways ( RAS, NF1, JAK ); tumor suppressors ( TP53, WT1 ) and transcription factor ( NOTCH1, RUNX1 and GATA2 ). Notably, mutations in NPM1 and PAX5 , which are the most common mutations in AML 27 and ALL 28 , respectively, were not seen in any patient in either of the described cohorts or in the cases presented in this report suggesting that these mutations may confer lineage specificity, an observation made by other recent investigators 29 . MPAL with TP53 mutations may represent inappropriate classification of therapy-related myeloid neoplasms as MPAL given that mutations in this gene are strongly associated with prior cytotoxic exposure and rarely seen in de novo leukemia 5, 30 .…”
Section: Discussionsupporting
confidence: 72%
“…Yan et al 19 reported on somatic mutations in 31 MPAL patients identifying ALL-type mutations including: IKZF1 (4/31), NOTCH (1/31), CDKN2A (4/12), EZH2 (3/31), ASLX1 (3/31) while no patient had mutations in common AML associated genes: NPM1, FLT3, DNMT3A, IDH1 or IDH2. Eckstein et al 26 identified mutations in 21/23 MPAL cases using whole exome sequencing and found that DNMT3A was the most frequently mutated gene (6/23). Investigators grouped MPAL alleles into three functional groups including cell signaling pathways ( RAS, NF1, JAK ); tumor suppressors ( TP53, WT1 ) and transcription factor ( NOTCH1, RUNX1 and GATA2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comprehensive study of 110 MPAL cases , rearrangement of the ZNF384 gene was present in 48% of B/myeloid MPAL involving various partner genes such as TCF3, EP300, CREBBP, and TAF15 . Single cases with various fusion transcripts have been found such as t(6;14)(q25,q32) , t(6;14)(q25,q24), t(12;17)(p13;q21) TAF15‐ZNF384 , t(7;14)(q32;q11.2) , t(10,11)(p15;q21), as well as aberrancies of chromosomes 5,6, 7,9, 16, and 17. Some of these are often seen in MDS.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…We may be dead wrong in recognition of MPAL so far, when it comes to the old concepts as compared to in real genetic aspects of mixed-phenotype or mixed-lineage and beyond. In the near future, we should redefine AML/ALL patients with bilineage clonal hematopoiesis as a novel and distinct high-risk group of patients that can be identified early at diagnosis through multi-modality diagnostic studies on hand [10], and as to focus on more specifically accurate target therapies with or without transplantation.…”
mentioning
confidence: 99%